Did they Find it? Developing a Revised Materials Availability Survey - Tang, Karen (Association of Research Libraries, 2014)
The purpose of this paper is to report on work being done by Curtin University in Perth, Western Australia to bring up to date an old library idea: the “materials availability survey.”